BIODEGRADASI FENANTREN OLEH BAKTERI LAUT Pseudomonas sp KalP3b22 ASAL KUMAI KALIMANTAN TENGAH - Murniasih, Tutik; Yopi, Yopi; Budiawan, Budiawan (UI Scholars Hub, 2009)
The Biodegradation of Phenanthren by Marine Bacteria Pseudomonas sp KalP3b22 from Kumai Central Borneo. The study of the potential marine bacteria that degrade Polycyclic Aromatic Hydrocarbons (PAHs) was already done among several marine bacterium isolated from the contaminated sea water collected in Kumai Port area. The biodegradation rate of phenanthrene by selected bacteria Pseudomonas sp Kalp-3b22 was 59,5% after 29 days cultivation. The structural determination of degradation product was deduced as 1-naphtalenol.